PENGARUH REPUTASI AUDITOR DAN JENIS KEPEMILIKAN PERUSAHAAN PADA VOLUNTARY DISCLOSURE LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Anggani, Putu Ayu Rara; Suartana, I Wayan; Dwija P, IGAM Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 05.NO.06. TAHUN 2016, 2016)
This research has the purpose to obtain empirical evidence of the influence of the auditor's reputation and the type of ownership of the voluntary disclosure annual report manufacturing company in Indonesia Stock Exchange. Determination of sample data using purposive sampling method. With purposive sampling method sample was 106 company with years of observation 2012. Multiple regression analysis is a technique of analysis used in this research. Test results prove the reputation variable auditors, internal ownership and ownership of non-governmental institutions affect the voluntary disclosure. While the government institutional ownership has no effect on voluntary disclosure.
Keywords: Reputation Auditor, Internal Company Ownership, Institutional Ownership Government, Non-Government Institutions Ownership